All Days 2009
DOI: 10.2118/125311-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized Mud Cap Drilling Drastically Reduces Non-Productive Time in Soka Field, South Sumatera

Abstract: The wells in Soka field in onshore South Sumatra, Indonesia are drilled through a fractured carbonate reservoir (Baturaja formation) where severe circulation losses and kicks while drilling are commonplace. Drilling in one of the wells in the field, Soka 2006–1 was suspended for two years due to total losses combined with gas kicks. Almost two months were spent after total loss of circulation was experienced trying to control and drill Soka 2006–1 to no avail. The well was plugged and abandoned on July 2006 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…[ 3 ] Field experiences showed that PMCD operation was successful in reducing formation damage, Non‐Productive Time (NPT), costs and risks when compared to conventional drilling operation. [ 9–14 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] Field experiences showed that PMCD operation was successful in reducing formation damage, Non‐Productive Time (NPT), costs and risks when compared to conventional drilling operation. [ 9–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3] Field experiences showed that PMCD operation was successful in reducing formation damage, Non-Productive Time (NPT), costs and risks when compared to conventional drilling operation. [9][10][11][12][13][14] Challenges associated with unconventional operations and the importance of developing monitoring, modeling and control studies seeking drilling automation were presented. [15,16] Online monitoring strategies, employing electro-magnetic transmission, pressure while drilling (PWD) and Mud-logging tools were developed.…”
Section: Introductionmentioning
confidence: 99%
“…When a kick is noted, the bullheading starts in order to force the gas influx back into the formation, ensuring a safe control of the operation under fractured zones (Carvalho et al 2019). Once a surface backpressure is exerted to compensate for the LAM column hydrostatic, which is slightly lower than reservoir pore pressure, gas migration can be monitored by pressure changes, enabling bullheading cycles to be performed, as soon as the maximum limit of annulus pressure is reached (Runtuwene et al 2009).…”
Section: Introductionmentioning
confidence: 99%